2016
DOI: 10.1186/s10194-016-0609-x
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone blocks interleukin 1 beta induced calcitonin gene related peptide release in trigeminal ganglia cells

Abstract: BackgroundMethylprednisolone (MPD) is a rapid acting highly effective cluster headache preventive and also suppresses the recurrence of migraine attacks. Previously, we could demonstrate that elevated CGRP plasma levels in a cluster headache bout are normalized after a course of high dose corticosteroids. Here we assess whether MPD suppresses interleukin-1β (IL-1β)- and prostaglandin E2 (PGE2)-induced CGRP release in a cell culture model of trigeminal ganglia cells, which could account for the preventive effec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
1
15
1
6
Order By: Relevance
“…31 A previous in vivo study suggested that IL-1β can promote powerful activation and mechanical sensitization of meningeal nociceptors and direct application of IL-6 to the dura produced a dose-dependent facial and hind-paw allodynia. 13,33 Another study demonstrated that local administration of TNF-α promoted an increase in the responses of meningeal nociceptors to mechanical stimulation of their dural receptive field and neuronal discharges. 34 In in vitro studies, it has been observed that TNF-α can promote the expression of CGRP and BDNF in trigeminal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…31 A previous in vivo study suggested that IL-1β can promote powerful activation and mechanical sensitization of meningeal nociceptors and direct application of IL-6 to the dura produced a dose-dependent facial and hind-paw allodynia. 13,33 Another study demonstrated that local administration of TNF-α promoted an increase in the responses of meningeal nociceptors to mechanical stimulation of their dural receptive field and neuronal discharges. 34 In in vitro studies, it has been observed that TNF-α can promote the expression of CGRP and BDNF in trigeminal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The release of vasoactive neuropeptides, in particular CGRP from both central and peripheral trigeminal terminals modulates the activity of second order neurons of the trigeminal nucleus caudalis [ 39 ] and increases meningeal blood flow [ 9 , 35 ]. Hence, measurements of the changes in dural blood flow in vivo, and the release of CGRP from meningeal sensory nerves in vitro, are reliable indicators of the activation of trigeminal nociceptive primary sensory neurons [ 9 , 40 42 ]. Endovanilloids are defined as endogenous ligands of the TRPV1 receptor and are synthetized or may be taken up by sensory ganglion neurons [ 30 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…106 In rat models of abdominal surgery and of parasite infection, significant changes in IL-1β and microglia activation were detected in the brain 3 weeks after insult, but changes in IL-6 were not detected. 107,108 Although we did not observe an IL-6 response, it is intriguing that IL-1β, 99,109 IL-6, 110,111 TNF-α, 112,113 IL-10, and TGF-β 114 have all been linked to pain mechanisms or headaches via calcitonin gene-related peptide. Post-traumatic headaches can increase the amount of time needed for cognitive recovery from TBI, 115 are often part of PCS, 26 and can be associated with sensory hypersensitivity 24 and inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 67%